AVALIAÇÃO DA EFICIÊNCIA ENERGÉTICA DE MATRIZES NELORADAS NA FAZENDA UEMS - SANTOS, Marrony Gonçalves Pires,; FERNANDES, Henrique Jorge,; BEZERRA, Thais dos Santos,; SILVA, Gislaine Jara,; SILVA, Camila de Souza,; TEIXEIRA, Edvan Correia, (ANAIS DO ENIC, 2024)
-